2018
DOI: 10.1097/mbc.0000000000000678
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin generation estimates the anticoagulation effect of direct oral anticoagulants with significant interindividual variability observed

Abstract: : Direct oral anticoagulants (DOACs) are increasingly being used, primarily due to their drug stability and patient convenience. Although these drugs have been evaluated to be well tolerated in numerous clinical trials, their impact on in-vivo anticoagulation effect, variability and therapeutic drug level remains unknown. Hence, we aim to study the effect and variability of DOACs on thrombin generation via the calibrated automated thrombogram. Anonymized coagulation specimens from outpatients on warfarin were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 34 publications
1
25
0
1
Order By: Relevance
“…Tailoring drug dosages to fit the needs of individual patients could be helpful to make old and new drugs more effective and safer . Preliminary observations showed that thrombin generation testing is affected by all anticoagulant drugs and therefore it could be the candidate assay . The test has been found to be very sensitive to all kind of anticoagulants and may best represent the interindividual response than just exploring plasma drug concentrations .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tailoring drug dosages to fit the needs of individual patients could be helpful to make old and new drugs more effective and safer . Preliminary observations showed that thrombin generation testing is affected by all anticoagulant drugs and therefore it could be the candidate assay . The test has been found to be very sensitive to all kind of anticoagulants and may best represent the interindividual response than just exploring plasma drug concentrations .…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary observations showed that thrombin generation testing is affected by all anticoagulant drugs and therefore it could be the candidate assay . The test has been found to be very sensitive to all kind of anticoagulants and may best represent the interindividual response than just exploring plasma drug concentrations . In addition to considering the interindividual response to an antithrombotic drug, thrombin generation testing is also able to explore in more detail the effect of anticoagulants on the coagulation process.…”
Section: Discussionmentioning
confidence: 99%
“…44 Finally, although a therapeutic range has not been established for DOACs, recent studies demonstrate that levels in extreme ranges (too low, or too high, compared to the published "on therapy" levels) are associated with clinical outcomes as bleeding or thrombosis. [45][46][47] Since several studies have found large inter-individual variation in drug levels it could be argued that a functional assay would give additional information on this patient's individual coagulation status.…”
Section: Oral Anticoagulant Therapy -Direct Oral Anticoagulantsmentioning
confidence: 99%
“…The correlation between the different doses of DOACs and measured drug levels is rather weak, reflected by broad "on-therapy" ranges. 50,[52][53][54] Although for some DOACs drug levels are associated with clinical outcome, such as bleeding and thrombosis [45][46][47] , this has not been translated into a clinically useful therapeutic window.…”
Section: Oral Anticoagulant Therapy -Direct Oral Anticoagulantsmentioning
confidence: 99%
See 1 more Smart Citation